Experimental Approach on the Cognitive Perception of Historic Urban Skyline - H. Bostancı, Seda; Oral, Murat (ICONARCH International Congress of Architecture and Planning, 2017)
In a lifetime, human brain constitutes cognitive models for various conditions and events in order to be able to adapt to the environment and lead a life based on experiences. Based on multidimensional sensory experiences, people create an internal model of a city and they use this model as a mental sketch in their new urban space experiences. Cognitive mapping methods create qualified data for way-finding and the process of classifying the stimuli of the living area and carrying out spatial designs that promote quality of life. Aesthetic perception of the urban pattern consists of keeping the skylines of a city in memory and being able to create an image in mind. Urban skylines can be classified basically in three categories as the historic skyline, complex skyline in which new and higher structures are dominant and mixed skyline which is a combination of these two situations. The aim of the study is to investigate how the image created by the skylines of historic cities can be expressed by drawing. The basic differences among the cognitive mapping techniques and the cognitive perception and the schematic display of a skyline can be discussed through this experimental approach. This study aims to do experimental research among a group of architecture students who are strong at drawing and schematic expressions. The selected group of samples will be asked to draw (1) the schematic skyline images of the city they live in and a city they have visited as far as they remember, (2) examined how they draw a skyline and how much time it takes after they are shown a skyline of a historic city chosen in a certain time, (3) watch a video on the streets of two different cities they have seen or haven’t seen before, and asked to draw a skyline of the city based on what they have watched. Finally, these different situations will be analysed. In the experimental study, After 3 days, drawing the best remembered skyline image will be requested from students. And what the sample group have thought in this selection in terms of aesthetics will be measured with the semantic differential and the adjective pairs. Participants will be asked to draw the catchy image of the skyline shown in order to compare the experimental methods and the subjective aesthetic evaluation methods. Observation-based determinations will be realized by the analysis of these drawings and the adjective pairs. In this way, the relation between the skyline perception and the aesthetic experience in urban life will be discussed.